2020
DOI: 10.47391/jpma.283
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to investigate the level of cognitive impairment among epileptic and psychogenic non-epileptic patients

Abstract: Abstract Objective: To compare cognitive impairment between patients having epileptic seizures and those having psychogenic non-epileptic seizures. Methods: The cross-sectional study was conducted from May to November 2016 in Jhelum, Pakistan, and comprised epileptic and psychogenic non-epileptic patients who were selected from different psychiatric units of the city. Bender Gestalt Test-II was administered to check the cognitive impairment of participants.   Data was analysed using SPSS 21. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The studies conducted in Indonesia about cognitive impairment among patients with epilepsy indicate the prevalence of cognitive impairment varies from 17.6% to 83.9% (Lestari et al, 2020; Zhu et al, 2022). A comparative study in Pakistan indicates that Epileptic patients have more cognitive impairment than psychogenic non-epileptic patients (Kausar et al, 2021). A similar study in Pakistan also indicated that 39.5% of patients with epilepsy had experienced cognitive impairment secondary to epilepsy (Malik et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies conducted in Indonesia about cognitive impairment among patients with epilepsy indicate the prevalence of cognitive impairment varies from 17.6% to 83.9% (Lestari et al, 2020; Zhu et al, 2022). A comparative study in Pakistan indicates that Epileptic patients have more cognitive impairment than psychogenic non-epileptic patients (Kausar et al, 2021). A similar study in Pakistan also indicated that 39.5% of patients with epilepsy had experienced cognitive impairment secondary to epilepsy (Malik et al, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Mood and objective cognitive function are both important contributors to subjective cognitive function [45] . While people with FS may complaint from impaired cognition (more than that by healthy controls), their cognitive impairment is usually not as bad as that in patients with epilepsy [46] , [47] , [48] . Nonetheless, cognitive impairment in patients with FS have potentially important clinical implications [49] .…”
Section: Impaired Cognitionmentioning
confidence: 99%